eFAKTOR-FAKTOR YANG MEMPENGARUHIPERMINTAANKONSUMEN TERHADAP IKAN TONGKOLDI TIKU KECAMATAN TANJUNG MUTIARA KABUPATENAGAM - Sitilamsyari, Bella; Asrizal, Asrizal; Jolianis, Jolianis (Pendidikan Ekonomi, 2014)
ABSTRACTÂ BELLA SITILAMSYARI(NIM:0909026) Factors Affecting Demand Consumers Against Tuna Fish In Tiku Agam District of Tanjung MutiaraÂ This study aims to determine the factors- actors that affect consumer demand for tuna in Tiku Agam District of Tanjung Mutiara. Where the independent variable is the price of swordfish (X1), the price of tilapia (X2), and population (X3) affect demand for swordfish (Y) as the dependent variable. The hypothesis of this study is tuna prices negatively affect the demand for tuna, while the price of tilapia and population positive effect on demand for tuna . The data used in this study are secondary data from the years 1983-2012, using data BPS publications, Fisheries and Food Security Agency Agam and supported by literature study by collecting data in accordance with the scope of the discussion . The data analysis technique used is the logarithmic regression equation to test the assumptions of classical statistics and test. The analysis model is expressed logy = log a+b3logX3+b2logX2+b1logX1+e. Based on the research results , obtained by the regression equation : logy = 27.176 to 3.082+logX1+2.569+7.215 logX2 logX3. In the classical assumption test, normal distribution of data, not the case heterosdastisitas, free multikolonieritas regression model, linearity test revealed a linear form and contain no autocorrelation problem. Variable price swordfish (X1), the price of tilapia (X2), and population (X3) based test of F > F table , where all independent variables simultaneously affect the dependent at the 5% significance level. While partially variable rates tuna and a significant negative effect on the demand for tuna, tilapia variable positive and significant effect on the demand swordfish, and a variable number of the population and a significant positive effect on the demand for tuna.